2019
DOI: 10.1038/s41416-019-0594-3
|View full text |Cite
|
Sign up to set email alerts
|

Monozygotic twins with neuroblastoma MS have a similar molecular profile: a case of twin-to-twin metastasis

Abstract: Fetoplacental neuroblastoma metastasis has been postulated as a mechanism accounting for concordant cases where one twin develops a primary tumour and the second twin manifests the disease without an identifiable primary site. These tumours may originate and spread concomitantly due to the same genetic background shared by monozygotic twins. This study investigated the molecular profile of stage MS neuroblastoma presenting concomitantly in monozygotic twins. Comparative genomic hybridisation (aCGH) was done fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Although the accurate reason for the origins of the same tumors at a similar time in multiples is not well known yet, there are two hypotheses explaining that phenomenon. The first theory suggests that tumors in twins arise from transplacental spread [ 20 , 21 ]. In a publication by Shatar et al, such a mechanism was suggested in a case of twins with neuroblastoma, where one twin developed a primary tumor, and the other had metastatic disease without a clear primary location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the accurate reason for the origins of the same tumors at a similar time in multiples is not well known yet, there are two hypotheses explaining that phenomenon. The first theory suggests that tumors in twins arise from transplacental spread [ 20 , 21 ]. In a publication by Shatar et al, such a mechanism was suggested in a case of twins with neuroblastoma, where one twin developed a primary tumor, and the other had metastatic disease without a clear primary location.…”
Section: Discussionmentioning
confidence: 99%
“…The signature of copy number changes in the tumors of both twins was similar and suggested a common clonal origin. Additional findings included large deletion of chromosome 10 and amplification of chromosome 17 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%